Determination of Maxillary and Mandibular Arch Width in Angle’s Class I Patients - Yadav, Anil K; Yadav, Rajiv; Pokhrel, Narayan; Yadav, Poonam K (Nepal Journal of Health Sciences, 2024)
Introduction: The transverse dimension plays a key role in smile. Maintaining the pretreatment arch form is a key to obtaining stable results.Objectives: The main aim of this study was to determine mean intercanine arch width and mean intermolar arch width in Angle’s class I patients.Methods: Seventy-six pretreatment casts were obtained from the records of patients who sought orthodontic treatment in Orthodontics and Dentofacial Orthopedics. Four parameters were used in this study namely; intercanine arch width and intermolar arch width in maxilla and mandible. Linear measurements were carried out with digital caliper. Kappa test was done for intra-observer reliability. Shapiro-Wilk test was done to determine the normal distribution of data. The Pearson Correlation test was done to assess the correlation between intercanine and intermolar arch width in maxilla and mandible. The independent t-test was used to compare between intercanine and intermolar arch width with male and female.Results: Mean intercanine arch width in maxilla and mandible were 35.41±1.47 mm and 26.85±1.59 mm respectively. Mean intermolar arch width in maxilla and mandible were 53.82±2.82 mm and 51.71±2.60 mm respectively. Statistically significant difference was found between intercanine and intermolar arch width in maxilla and mandible between male and female. The intercanine and intermolar arch width in maxilla and mandible has significantly low correlation.Conclusions: Intercanine and intermolar arch width in male and female were statistically significant and male has lager intercanine and intermolar arch width than female.